Equity-oriented design in open education. Issue 5 (5th November 2018) - Kalir, Jeremiah Holden
Abstract : Purpose: The purpose of this paper is threefold: to describe the equity-oriented design of a publicly accessible and openly networked computer-supported collaborative learning (CSCL) initiative that has supported educator discussion about equity topics; to identify design principles for equity-oriented design in open education; and to propose a model for the design of open learning initiatives that are mutually committed to educational equity and educational openness. Design/methodology/approach: This paper draws from design-based research methodology, specifically design narrative and the worked example. The paper is one response to the need for more "designerly work" in the learning sciences, generally, and more specifically in domains such as CSCL. Findings: Four design principles are identified that informed the equity-oriented creation and iteration of the Marginal Syllabus, an open CSCL initiative: leveraging the open web, fostering multi-stakeholder partnerships, working with open content and engaging professional learning as an open practice. This paper also advances the open palimpsests model for equity-oriented design in open education. The model integrates design principles to assist CSCL and open education designers and researchers in creating or iterating projects to be more equity-oriented learning opportunities. Originality/value: This paper's design narrative identifies Marginal Syllabus design principles and advances the open palimpsests model for equity-oriented design in open education. The design narrative demonstrates how critical perspectives on the relationship between equity and digital technology can encourage collaboration among diverse project stakeholders, attune to the dynamics of power and agency and respond to the worldly needs of partners and participants.